2010
DOI: 10.1093/nar/gkq1073
|View full text |Cite
|
Sign up to set email alerts
|

ASPicDB: a database of annotated transcript and protein variants generated by alternative splicing

Abstract: Alternative splicing is emerging as a major mechanism for the expansion of the transcriptome and proteome diversity, particularly in human and other vertebrates. However, the proportion of alternative transcripts and proteins actually endowed with functional activity is currently highly debated. We present here a new release of ASPicDB which now provides a unique annotation resource of human protein variants generated by alternative splicing. A total of 256 939 protein variants from 17 191 multi-exon genes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
(66 reference statements)
0
29
0
Order By: Relevance
“…Using the parental genes of the IR-type duplicates that contain one or more of the parental introns (seven in Drosophila spp., 55 in human, 92 in rice, and 200 in Arabidopsis), we searched the AS databases (DEDB [Lee et al, 2004] for Drosophila spp., ASPicDB [Martelli et al, 2011] for human, and ASIP [Wang and Brendel, 2006] for rice and Arabidopsis), which use RNA sequencing, EST, and cDNA support to identify AS isoforms, following the steps detailed in "Materials and Methods." We identified three, 86, 47, and 32 parental genes with intron retention AS isoforms for Drosophila spp., human, rice, and Arabidopsis, respectively.…”
Section: As Parental Isoforms Support As-based Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the parental genes of the IR-type duplicates that contain one or more of the parental introns (seven in Drosophila spp., 55 in human, 92 in rice, and 200 in Arabidopsis), we searched the AS databases (DEDB [Lee et al, 2004] for Drosophila spp., ASPicDB [Martelli et al, 2011] for human, and ASIP [Wang and Brendel, 2006] for rice and Arabidopsis), which use RNA sequencing, EST, and cDNA support to identify AS isoforms, following the steps detailed in "Materials and Methods." We identified three, 86, 47, and 32 parental genes with intron retention AS isoforms for Drosophila spp., human, rice, and Arabidopsis, respectively.…”
Section: As Parental Isoforms Support As-based Modelmentioning
confidence: 99%
“…plantgdb.org/ASIP/; 2007 version; Brendel, 2006), human (2028) from ASPicDB (http://t.caspur.it/ASPicDB/; Martelli et al, 2011), and Drosophila spp. (2386) from DEDB (http://proline.bic.nus.edu.sg/dedb; Lee et al, 2004).…”
Section: Identifying Ir-type Genes With As Supportmentioning
confidence: 99%
“…Sequence alignment was performed with the programs of MultAlin and ESPript. were predicted (39,40). We checked the alternative transcripts of these PA28 members deposited in GenBank, and found that four transcript variants of PA28α, one transcript variant of PA28β and four transcript variants of PA28γ have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, three homologs of proteasome activator PA28α, PA28β, and PA28γ were shown to have upregulated mRNA levels in oral squamous cell carcinoma (OSCC) cells relative to oral keratinocytes (38). In this study, we analyzed alternative splicing of PA28γ using the alternative splicing prediction data base ASPicDB (39,40), and found that there are theoretically nearly 50 alternative transcripts. we therefore tried cloning these predicted splice variants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have extracted from the literature the relevant information on the genome coordinates of RNA binding sites (or experimentally validated non-binding sites), type of binding assay, gene information and the context-specific splicing effects of splicing factor binding in terms of exonization or intronization. Furthermore, binding site information have been also reported in the transcript view of ASPicDB [1,3].…”
Section: Methodsmentioning
confidence: 99%